The Influence of Character Image to Word-of-Mouth Through Gamer Satisfaction of Impulse Spending in the Genshin Impact Mobile Game - Reynaldo, Kevin; Salehudin, Imam (Bina Nusantara University, 2024)
This research aims to understand the influence of character image (symbolic representation and self-image congruence) on impulse buying and satisfaction in word-of-mouth recommendations for the game Genshin Impact in Indonesia. Hence, the study explored the potential of character image by spreading online survey to gen Z Genshin Impact gamers in Indonesia. The hypotheses in this study were tested using Structural Equation Modelling (SEM) with Lisrel 8.8. The significant results of this study to show character image have positive influence between impulse buying, satisfaction, and word-of-mouth. Character image is one of the important factors in increasing revenue for game companies, as seen in Genshin Impact, where the selling point of sales come from in-game character that make the company’s revenue increase.